PONV management in patients with QTc prolongation on the EKG - Soghomonyan, S.; Stoicea, N.; Ackermann, W.; Bhandary, S. P. (Frontiers in Pharmacology, 2021)
Postoperative nausea and vomiting (PONV) is a commonly encountered problem in the postoperative period. It delays discharge from the unit, requires additional resources to treat and may increase morbidity in some patients. Many effective drugs are available to treat or prevent PONV, however many of these drugs have the potential to increase the QTc on the electrocardiogram. The QTc prolongation, in turn, may predispose to development of serious ventricular arrhythmias, in particular, torsade de pointes (TdP). The QTc prolongation may be a manifestation of a genetic mutation resulting in abnormal myocyte repolarization or it may be acquired and associated with the use of various medications, electrolyte disorders, and physiological conditions. Patients susceptible to QTc prolongation presenting for surgery constitute a challenging group, since many drugs commonly used for PONV management will put them at risk for perioperative serious arrhythmias. This is an important topic, and current manuscript is an attempt to describe the problem, summarize existing experience and generate recommendations for safe perioperative PONV management for patients at increased risk for QTc prolongation and arrhythmias. Focused prospective studies will help to find definitive answers to the discussed problems and challenges.